Human milk microbiome: associations with maternal diet and infant growth - Ajeeb, Tamara T.; Gonzalez, Emmanuel; Solomons, Noel W.; Vossenaar, Marieke; Koski, Kristine G. (Frontiers in Nutrition, 2024)
Introduction: Ingestion of human milk (HM) is identified as a significant factor associated with early infant gut microbial colonization, which has been associated with infant health and development. Maternal diet has been associated with the HM microbiome (HMM). However, few studies have explored the associations among maternal diet, HMM, and infant growth during the first 6 months of lactation.Methods: For this cross-sectional study, Mam-Mayan mother-infant dyads (n=64) were recruited from 8 rural communities in the Western Highlands of Guatemala at two stages of lactation: early (6-46 days postpartum, n = 29) or late (109-184 days postpartum, n = 35). Recruited mothers had vaginally delivered singleton births, had no subclinical mastitis or antibiotic treatments, and breastfed their infants. Data collected at both stages of lactation included two 24hr-recalls, milk samples, and infant growth status indicators: head-circumference-for-age-z-score (HCAZ), length-for-age-z-score (LAZ), and weight-for-age-z-score (WAZ). Infants were divided into subgroups: normal weight (WAZ≥-1SD) and mildly underweight (WAZ<-1SD), non-stunted (LAZ≥1.5SD) and mildly stunted (LAZ<-1.5SD), normal head-circumference (HCAZ≥-1SD) and smaller head-circumference (HCAZ<-1SD). HMM was identified using 16S rRNA gene sequencing, amplicon analysis was performed with the highresolution ANCHOR pipeline, and DESeq2 identified the differential abundant (DA) HMM at the species-level between infant growth groups (FDR < 0.05) in both early and late lactation.Results: Using both cluster and univariate analyses, we identified a) positive correlations between infant growth clusters and maternal dietary clusters, b) both positive and negative associations among maternal macronutrient and micronutrient intakes with the HMM at the species level and c) distinct correlations between HMM DA taxa with maternal nutrient intakes and infant z-scores that differed between breast-fed infants experiencing growth faltering and normal growth in early and late lactation.Collectively, these findings provide important evidence of the potential influence of maternal diet on the early-life growth of breastfed infants via modulation of the HMM.